Distance invariant method for normalization of indexed differentials. (May 2021) - Liu, Jiang; Ni, Feng
Abstract: A distance from free to dummy indices is defined. The distance is invariant with respect to both monoterm symmetries and bottom antisymmetry. Using the distance invariant, we present an index-replacement algorithm. We then develop two normalization algorithms. One is with respect to monoterm symmetries and has complexity lower than known algorithms; the other allows one to determine the equivalence of indexed polynomials in the Einstein summation ring R 2 [ ∂̸ ] .